Examining the Role of Influencer Product and Consumer Congruence on Influencer Tasya Farasya - Beggie, Eudoxia Hosiyana; Darma, Gede Sri (Dinasti Publisher, 2024)
In the current digital era, there is a shift in marketing where everything is online, this requires business people to create marketing strategies in accordance with current trends such as marketing using influencers. This study aims to determine the effect of Influencer Product Congruence and Influencer Consumer Congruence on Intention to Purchase mediated through Attitude on Influencer Tasya Farasya. To determine the effect of Influencer Product Congruence and Influencer Consumer Congruence on Intention to Recommend mediated through Attitude on Influencer Tasya Farasya. This research is a type of quantitative research. The sample in this study was 260 respondents. The primary research data collection technique was carried out by distributing questionnaires using Google Form which were analyzed using the Structural Equation Model (SEM) approach. The results of the study indicate that there is a positive influence of Influencer Product Congruence and Influencer Consumer Congruence on Attitude, there is a positive influence of Attitude on Intention To Purchase and Intention To Recommend, there is a positive influence of Intention To Purchase on Purchase Decision and Repurchase Intention, there is an influence of Influencer Consumer Congruence and Influencer Consumer Congruence mediated by Attitude on Intention to Purchase, there is a positive influence of Influencer Product Congruence and Influencer Consumer Congruence mediated by Attitude on Intention To Recommend.